Kualitas Produk, Harga Dan Promosi Terhadap Keputusan Pembelian Pada E-commerce Bukalapak - Putri, Yulisa; Rahayu, Sri; Fitantina, Fitantina (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
The purpose of this study was to determine the effect of Product Quality, Price and Promotion on Purchasing Decisions on Bukalapak e-commerce in Baturaja Timur District simultaneously and partially. This type of research is associative research. The population is infinite and the sample is 100 respondents. The data used are Primary and Secondary data, using questionnaire and documentation data collection methods. The analysis technique used is Multiple Linear Regression, F and t Hypothesis Tests, and the Determination Coefficient. The results show that there is a positive influence of Product Quality, Price and Promotion on Purchasing Decisions on Bukalapak e-commerce in Baturaja Timur District.